1998
DOI: 10.1046/j.1365-8711.1998.01257.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term variability of the Be/X-ray binary A 0535+26 -- I. Optical and UV spectroscopy

Abstract: The results of a 7‐yr optical and UV spectroscopic study of the high‐mass X‐ray binary A 0535+26 are presented. It was found that throughout the period of the observations the line profile of Hα showed considerable variability. A correlation between the equivalent width of Hα and both V‐band magnitude and (B−V) colour excess was observed, albeit with considerable scatter present in the data set. A giant X‐ray flare in early 1994 was accompanied by a fading in optical and infrared photometric bands, and a reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 9 publications
3
43
2
Order By: Relevance
“…For ten sources from the target list, we complemented our observations with data taken before 1999. These spectra were obtained in the framework of the Southampton/Valencia collaborative project (Reig et al 1997a), where a number of telescopes were used: the 2.5 m Isaac Newton Telescope (INT) and the 1.0 m Jacobus Kapteyn Telescope (JKT), both located at the Roque de los Muchachos Observatory in La Palma, the 1.5 m at Palomar Mountain (PAL), the 1.9 m telescope of the South Africa Astronomical Observatory (SAAO), and the 2.2 m telescope at Calar Alto in Almería, Spain (CA), and resulted in numerous publications (Clark et al 1998(Clark et al , 1999(Clark et al , 2001Coe et al 1993Coe et al , 1996Gorrod et al 1993;Haigh et al 1999Haigh et al , 2004Negueruela et al 1997Negueruela et al , 1998Negueruela et al , 1999Norton et al 1991;Reig et al 1996Reig et al , 1997cReig et al , 2000Roche et al 1993a,b;Unger et al 1998). For the sake of homogeneity, we re-analysed all the spectra in a consistent way, as explained in the next section.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…For ten sources from the target list, we complemented our observations with data taken before 1999. These spectra were obtained in the framework of the Southampton/Valencia collaborative project (Reig et al 1997a), where a number of telescopes were used: the 2.5 m Isaac Newton Telescope (INT) and the 1.0 m Jacobus Kapteyn Telescope (JKT), both located at the Roque de los Muchachos Observatory in La Palma, the 1.5 m at Palomar Mountain (PAL), the 1.9 m telescope of the South Africa Astronomical Observatory (SAAO), and the 2.2 m telescope at Calar Alto in Almería, Spain (CA), and resulted in numerous publications (Clark et al 1998(Clark et al , 1999(Clark et al , 2001Coe et al 1993Coe et al , 1996Gorrod et al 1993;Haigh et al 1999Haigh et al , 2004Negueruela et al 1997Negueruela et al , 1998Negueruela et al , 1999Norton et al 1991;Reig et al 1996Reig et al , 1997cReig et al , 2000Roche et al 1993a,b;Unger et al 1998). For the sake of homogeneity, we re-analysed all the spectra in a consistent way, as explained in the next section.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…The long-term variability of optical and IR photometry was discussed by Hao et al (1996), Clark et al (1998Clark et al ( , 1999, Haigh et al (1999Haigh et al ( , 2004, and Lyuty & Zaitseva (2000). The variability of the Hα emission line is related to physical changes in the circumstellar disk around the Be star.…”
Section: Introductionmentioning
confidence: 96%
“…First it was assumed that the absence of X-ray outburst at the orbital phase φ = 0.0 is caused by the lower Be star activity and, correspondingly, the decrease of plasma density in the stellar envelope (Giovannelli & Graziati 1992). However, systematic multiwavelength studies of the system reported recently (Clark et al 1998a and references therein) did not confirm this hypothesis: "missing" flare phenomena occured during the period when the optical-IR flux of the star was increasing.…”
Section: Introductionmentioning
confidence: 92%
“…However, systematic optical-IR observations have shown the "missing" flare phenomena to occur also during the periods when the circumstellar disk is in its brightest state (see Clark et al 1998a). This suggests that the low activity of the Be star is not the only reason for the "missing" flare phenomenon and an additional factor, which leads to suppression of X-ray flaring at the periastron, operates in the system.…”
Section: "Missing" Flare Phenomenonmentioning
confidence: 99%